Environment and development in relations between Europe and Latin America : perception and works of NGOs - Agrasot, Paloma ed. (European Environment Bureau BrusselsBE, 1994)
Deals with the general impact of European relations in Latin America under such headings as development cooperation, debt, trade and investments. Discusses the plight of the cities, which is seen as one of Latin America's major problems. Describes the environment movement and the work of NGO'S